ANALISIS IKLAN MINUMAN DI KORAN BINTANG BORNEO PADA TAHUN 1930 - Aulia Rahuma; Rizaldi, Muhammad Irfan (Amarthapura: Historical Studies Journal, 2023)
The need for food and drink cannot be separated from our daily lives. Therefore, the community uses this to be used as a business by advertising these services in the mass media. Therefore, advertisements offering food and beverage products in the mass media are claimed to be good. In print media itself, in general, they advertise their products in the form of classified ads or often called mini ads that have relatively cheap rates.the number of advertisements in the newspaper every day and even every month is different in some newspapers which of course are quite a lot of advertisements by offering various kinds of food and drinks that exist. The author uses the case study method by means of a qualitative approach, this aims to find out the regulation or timeline of the advertisement and the practice of beverage products advertised through the Bintang Berneo newspaper in 1930 from March to July. The conclusion of this study is that regulations or timelines in advertising in mass media are not comprehensive. With the advertisement of drinks in the Bintang Borneo newspaper, it can provide useful information for the local community.